Population pharmacokinetics of recombinant human C1 inhibitor in patients with hereditary angioedema. (December 2013) - Farrell, Colm; Hayes, Siobhan; Relan, Anurag; van, Edwin S.; Pijpstra, Rienk; Hack, C. Erik
<x xml:space="preserve">Abstract</x> Aims To characterize the pharmacokinetics (PK) of recombinant human C1 inhibitor (rhC1INH) in healthy volunteers and hereditary angioedema (HAE) patients. Methods Plasma levels of C1INH following 294 administrations of rhC1INH in 133 subjects were fitted using nonlinear mixed‐effects modelling. The model was used to simulate maximal C1INH levels for the proposed dosing scheme. Results A one‐compartment model with Michaelis–Menten elimination kinetics described the data. Baseline C1INH levels were 0.901 [95% confidence interval (CI): 0.839–0.968] and 0.176 U ml−1 (95% CI: 0.154–0.200) in healthy volunteers and HAE patients, respectively. The volume of distribution of rhC1INH was 2.86 l (95% CI: 2.68–3.03). The maximal rate of elimination and the concentration corresponding to half this maximal rate were 1.63 U ml−1 h−1 (95% CI: 1.41–1.88) and 1.60 U ml−1 (95% CI: 1.14–2.24), respectively, for healthy volunteers and symptomatic HAE patients. The maximal elimination rate was 36% lower in asymptomatic HAE patients. Peak C1INH levels did not change upon repeated administration of rhC1INH. Bodyweight was found to be an important predictor of the volume of distribution. Simulations of the proposed dosing scheme predicted peak C1INH concentrations above the lower level of the normal range (0.7 U ml−1) for at least 94% of all patients. Conclusions The population PK model for C1INH supports a dosing scheme on a 50 U kg−1 basis up to 84 kg, with a fixed dose of 4200 U above 84 kg. The PK of rhC1INH following repeat administration are consistent with the PK following the first administration.